GPS-derived interseismic fault locking along the Jalisco–Colima segment of the Mexico subduction zone. Issue 3 (25th October 2021) - Cosenza-Muralles, B; DeMets, C; Márquez-Azúa, B; Sánchez, O; Stock, J; Cabral-Cano, E; McCaffrey, R
SUMMARY: Northeastward subduction of the oceanic Rivera and Cocos plates in western Mexico poses a poorly understood seismic hazard to the overlying areas of the North America plate. We estimate the magnitude and distribution of interseismic locking along the northern ∼500 km of the Mexico subduction zone, with a series of elastic half-space inversions that optimize the fits to the velocities of 57 GPS stations in western Mexico. All velocities were corrected for the co-seismic, afterslip and viscoelastic rebound effects of the 1995 Colima–Jalisco and 2003 Tecomán earthquakes. We explore the robustness of interseismic locking estimates to a variety of mantle Maxwell times that are required for the viscoelastic corrections, to the maximum permitted depth for locking of the subduction interface and to the location assigned to the Rivera–Cocos–North America plate triple junction offshore from western Mexico. The best-fitting locking solutions are associated with a maximum locking depth of 40 km, a triple junction location ∼50 km northwest of the Manzanillo Trough and a mantle Maxwell time of 15 yr (viscosity of 2 × 10 19 Pa s). Checkerboard tests show that the locking distribution is best resolved at intermediate depths (10–40 km). All of our inversions define a gradual transition from strong locking (i.e. 70–100 per cent) of most (70 per cent) of the Rivera–North America subduction interface to strong but less uniform locking below the Manzanillo Trough, where oceanic lithosphere transitional between the Cocos and Rivera plate subducts, to weak to moderate locking (averaging 55 per cent) of the Michoacán segment of the Cocos–North America interface. Strong locking of the ∼125-km-long trench segment offshore from Puerto Vallarta and other developed coastal areas, where our modelling indicates an average annual elastic slip-rate deficit of ∼20 mm yr −1, implies that ∼1.8 m of unrelieved plate slip has accrued since the segment last ruptured in 1932, sufficient for an M ∼ 8.0 earthquake.